2011
DOI: 10.4314/tjpr.v10i6.11
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities of Ethanol Extracts of <i>Cynara Scolymus (Cynarae folium, Asteraceae</i> Family)

Abstract: Purpose: Cynara scolymus is a medicinal plant frequently used in traditional medicine for stomach and liver diseases. The purpose of the study was to identify the most suitable extraction solvent for maximum antioxidant and antimicrobial effect of fluidized bed extracts. Methods: The extracts were obtained by conventional maceration and fluidized bed extraction using 25, 50, 75 and 97 % v/v ethanol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 12 publications
3
18
1
Order By: Relevance
“…However, according to Kollia et al, 8 the extraction method also has a significant impact on the antioxidant properties of artichoke leaf extracts, while the contribution of total phenolics content to antioxidant properties depends on the tested assay. Similar findings have been reported by Coinu et al, 7 Pistón et al, 11 and Vamanu et al, 41 who suggested that antioxidant potency depends on the extraction method and solvents and is not related to total phenolics or individual phenolic subclass content.…”
Section: Resultssupporting
confidence: 89%
“…However, according to Kollia et al, 8 the extraction method also has a significant impact on the antioxidant properties of artichoke leaf extracts, while the contribution of total phenolics content to antioxidant properties depends on the tested assay. Similar findings have been reported by Coinu et al, 7 Pistón et al, 11 and Vamanu et al, 41 who suggested that antioxidant potency depends on the extraction method and solvents and is not related to total phenolics or individual phenolic subclass content.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, the maximum amount of polyphenol was also obtained from Morinda citrifolia and Cynara scolymus by using 75 wt. % ethanol/water solvent (Vamanu et al, 2011;Thoo et al, 2013). This higher TPC or TFC, may be ascribed to the fact that ethanol can effectively increase the permeability of the cell wall, and water can cause further solubility of polar substances in the cell (Saenkod et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Ethanol extracts were evaporated to dryness in a rotary evaporator (R 210; Buchi, Flawil, Switzerland) with a vacuum controller (V-850; Buchi) at 50 o C, 175 mbar, and 200 rpm. Selected concentrated solutions were redissolved in 80% ethanol to yield solutions containing 0.2-1.0 mg of extract per mL solvent (4,(6)(7)(8).…”
Section: Methodsmentioning
confidence: 99%
“…It has been used especially to isolate aromatic compounds (3) and is used less for natural extracts. In the last few years, research has demonstrated increasing degrees of biological activity in extracts from medicinal plants (4,5). However, little research has focused on obtaining natural products via alternative extraction methods.…”
Section: Introductionmentioning
confidence: 99%